PENGARUH TAYANGAN TELEVISI TERHADAP PERILAKU AGRESIF ANAK USIA DINI DI KB KASIH BUNDA DESA SUMEDANGAN KECAMATAN PADEMAWU KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Tri Febriyani Handini; M. Ridlwan; Ratno Abidin (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the Effect of Television Shows on Aggressive Behavior in Early Childhood in the Kasih Bunda Family, Sumedangan Village, Pademawu District, Pamekasan Regency, in the 2021/2022 Academic Year. Television is a sophisticated electronic media that is widely consumed by the wider community. Through television, children can get a wider variety of information, while also getting much more enjoyable entertainment. The research method used in this study uses quantitative methods. Retrieval of research data using interview and observation data collection techniques. Data collection by interview was carried out starting from parents, family members, teachers, and children who behaved aggressively. The results of the research that have been conducted, it can be concluded that, There is an Influence of Television Shows on Aggressive Behavior of Early Childhood in the Kasih Bunda Family Planning Program, Sumedangan Village, Pademawu District, Pamekasan Regency for the 2021/2022 Academic Year.Â Keywords: Aggressive; quantitative; observation; impressions